How Teaching About Therapeutic Jurisprudence Can Be a Tool of Social Justice, and Lead Law Students to Personally and Socially Rewarding Careers: Sexuality and Disability as a Case Example - Lynch, Alison J. (SSRN eLibrary, 2015)
Therapeutic jurisprudence (TJ) asks us to look at law as it actually impacts people’s lives and focuses on the law’s influence on emotional life and psychological well-being. It suggests that law should value psychological health, should strive to avoid imposing anti-therapeutic consequences whenever possible, and — when consistent with other values served by law — should attempt to bring about healing and wellness. The ultimate aim of TJ is to determine whether legal rules and procedures or lawyer roles can or should be reshaped to enhance their therapeutic potential while not subordinating due process principles. An inquiry into therapeutic outcomes does not mean that therapeutic concerns ‘trump’ civil rights and civil liberties. TJ’s aim is to use the law to empower individuals, enhance rights, and promote well-being, And one of TJ’s central principles is a commitment to dignity. We know that, in many cases, law students’ desire to engage in pressing social issues fades as they become both disillusioned and passive over the course of their law school experience, and this disillusionment is often abetted by the attitudes of their professors and the way that law school is traditionally taught. We believe that the adoption of TJ principles is a way to end this disillusionment and help return students to a focus on social justice, as a way of better insuring more personally enriching and rewarding careers. In this paper, we consider this issue through the prism of teaching (and learning about) the intersection between sexuality and disability. In other articles, the authors have argued that the way society both (often simultaneously) demonizes and infantilizes persons with disability when questions of sexuality are raised reflects the level of sanism and pretextuality that permeates all of mental disability law. In these articles, we have argued further that a therapeutic jurisprudence perspective can best insure that the persons in question have voice, and are treated with dignity. In this paper, we discuss these issues, as well as examine the ways in which intersectionality — expanding our view to include factors such as race, sex, gender and sexual orientation — can compound the difficulty of discussing this topic. We seek to lay out a blueprint for other faculty members — senior, junior and future — to employ in teaching about marginalized populations, especially in substantive areas (such as this) that often evoke wildly negative reactions, even among classically “left/progressive” faculty and students